Sign of Leser-Trélat and Cutaneous T-Cell Lymphoma: A Rare Association - Raphaël André; Emmanuel Laffitte; Marem Abosaleh; Bégonia Cortès; Laurence Toutous-Trellu; Gürkan Kaya (MDPI AG, 2018)
Sign of Leser-Trélat is a rare paraneoplastic cutaneous manifestation, characterized by the sudden appearance and rapid increase in size and number of seborrheic keratoses, accompanied by pruritus. Edmund Leser and Ulysse Trélat described this sign in 1890. Since their first description, their conclusions have been considered controversial and some authors assert the absence of a causal link. It seems to be frequently associated with solid tumors and in particular gastrointestinal cancer. Here, we describe a new case associated with a cutaneous T-cell lymphoma and a partial response to extracorporeal photopheresis.